Physiological Responses of African Catfish Hybrid (Clarias gariepinus ♀×Heterobranchus bidorsalis ♂) to Dietary Coriander Supplementation - Jimoh, Wasiu Adeyemi; Ayeloja, Ayodeji Ahmed; Yusuf, Olatunji Yusuf; Abdulfatahi, Abdulrahman Ataragba (Journal of Fisheries and Environment, 2022)
Physiological responses of African catfish hybrid (Clarias gariepinus ♀×Heterobranchus bidorsalis ♂) to dietary coriander supplementation were evaluated in a 56-day feeding trial. Five isolipidic and isonitrogenous diets were formulated comprising a control (without coriander, DT1) and four test diets (supplementation of 0.5% coriander powder, (DT2), 1% (DT3), 1.5% (DT4), and 2% (DT5). The diets were allotted to triplicate groups of 15 fish (4.88±0.42 g average weight). The growth rate, carcass protein and lipid in the fish fed a 0.5% coriander-based diet were significantly higher (p<0.05) than those fed the control diet. The 0.5% coriander dietary group markedly (p<0.05) outperformed the other dietary groups in terms of protein, energy and lipid. The survival rate and flesh yield of the coriander-fed group were greater (p>0.05) than those of the control group. The levels of packed cell volume, hemoglobin content and red blood cells showed significant differences (p<0.05) among treatments, with the 0.5% dietary group showing the highest values for these parameters. Total protein and globulin levels in the 0.5 and 1% coriander-fed groups were greater (p<0.05) than those in the control group, while aspartate transaminase, alanine transaminase, alkaline phosphatase, urea and creatinine, and glucose were significantly (p<0.05) lower in the coriander supplementation group up to 1.5%. A 2nd-order polynomial regression revealed that a 0.55% dosage of coriander powder (%) would support optimum percentage weight gain.